Association between pregnancy intention and late initiation of antenatal care among pregnant women in Ethiopia: a systematic review and meta-analysis - Tadesse Tolossa (Systematic Reviews, 2020)
Abstract Background Antenatal care is one of the continua of reproductive health care, and inadequate antenatal care utilization results in an adverse feto-maternal outcome. Pregnancy intention is an essential factor that plays a paramount role on timing of antenatal care service. The finding of a few studies conducted on the association between pregnancy intention and late initiation of ANC among pregnant women in Ethiopia presented inconclusive. Therefore, the objective of this systematic review and meta-analysis was to determine the pooled estimate of the association between pregnancy intention and late initiation of ANC among pregnant women in Ethiopia. Methods Both published and unpublished studies were accessed through electronic search from databases such as MEDLINE, Scopes, PubMed, CINAHL, PopLine, MedNar, Cochrane library, the JBI Library, the Web of Science, and Google Scholar. All observational studies that were conducted on the association between pregnancy intention and late initiation of ANC among pregnant women in Ethiopia were included. STATA 14.1 version was used for data analysis. A random effects model was used to estimate the pooled estimate with a 95% confidence interval (CI). The Cochrane Q test statistic and I 2 tests were used to assess heterogeneity. Presence of publication bias was checked by funnel plots and Egger’s statistical tests. Results A total of 670 published and unpublished studies were identified from several databases and fourteen studies fulfilled inclusion criteria and included in the meta-analysis. The overall pooled estimate indicates the odds of late initiation of antenatal care were 2.16 times higher among pregnant women who had unintended pregnancy as compared to pregnant women who had intended pregnancy (OR 2.16, 95% CI 1.62, 2.88). Conclusion The systematic review and meta-analysis found a statistically significant effect of pregnancy intention on late initiation of antenatal care among pregnant women in Ethiopia. Increased effort should be made to improve women’s behavior towards contraceptive use through health education and counseling, especially those with unintended pregnancies. Furthermore, health education, counseling, and communication campaigns related to the timing of ANC and frequency should be promoted nationally.